Desain Sampul Majalah sebagai Ujung Tombak Pemasaran - Widyokusumo, Lintang (Humaniora, 2012)
Amid the proliferation of electronic media competition, the role of conventional media such as magazines still becomes a promising choice. The recency of printing techniques, finishing and layout software currently enable more rapid publication of a magazine. Its presence in every corner of the city increasingly makes it easier for consumers to buy and makes it a complete source of information plus attractive bonus which is always a tempting offer in each issue. Amid the hundreds of magazine design magazine rack is on store / stall / supermarket sales how can a magazine survive? Surely, the role of creativity of magazine cover designs as a bridge of communication to the customers becomes the forefront of marketing which is highly important.